Gas Chromatography-Tandem Mass Spectrometry Method for the Selective Detection of Glycols and Glycerol in the Liquids and Aerosols of E-Cigarette, or Vaping, Products - Pérez, José J.; Watson, Clifford H.; Blount, Benjamin C.; Valentín-Blasini, Liza (Frontiers in Chemistry, 2021)
The long-term health effects of using e-cigarette, or vaping, products (EVPs; also known as e-cigarettes, electronic nicotine delivery systems, and vape pens) remain largely unknown. The inhalation of excipients, such as propylene glycol (PG) and glycerin (GLY), may have long-term health effects. In addition to the direct health effects of PG and GLY, glycerin-containing products can be contaminated with toxic ethylene glycol (EG) and diethylene glycol (DEG). To assess this issue, we developed a simple, versatile, high-throughput isotope dilution gas chromatography-tandem mass spectrometry method for quantifying these common excipients and contaminants. The method is applicable to both the liquid contents and machine-generated aerosols of EVPs. Our rigorous method validation demonstrates that the new method is specific, precise, accurate, and rugged/robust. The calibration range is linear from 0.1–7 mg for the excipients and 2.5–1000 µg for the contaminants. These ranges encompass expected excipients levels in EVP e-liquids and their machine-generated aerosols and the relevant maximum residue safety limit of 1 mg/g, or 0.1% (w/w), for the contaminants. The calculated limits of detection for PG, GLY, EG, and DEG were determined as 0.0109 mg, 0.0132 mg, 0.250 µg, and 0.100 µg, respectively. The method was applied to the aerosol emissions analysis of 141 EVPs associated with the 2019 lung injury outbreak, and found typical levels of PG (120.28–689.35 mg/g of aerosol) and GLY (116.83–845.96 mg/g of aerosol) in all nicotine-containing products; PG (81.58–491.92 mg/g of aerosol) and GLY (303.86–823.47 mg/g of aerosol) in 13% of cannabidiol (CBD) products; PG (74.02–220.18 mg/g of aerosol) and GLY (596.43–859.81 mg/g of aerosol) in products with neither nicotine nor CBD; and none detected in tetrahydrocannabinol (THC) products. No products contained glycol contaminants above the recommended maximum residue safety limit.